Molecular Profile of Variants Potentially Associated with Severe Forms of COVID-19 in Amazonian Indigenous Populations - Rita de Cássia Calderaro Coelho; Carlliane Lima e Lins Pinto Martins; Lucas Favacho Pastana; Juliana Carla Gomes Rodrigues; Kaio Evandro Cardoso Aguiar; Amanda de Nazaré Cohen-Paes; Laura Patrícia Albarello Gellen; Francisco Cezar Aquino de Moraes; Maria Clara Leite Calderaro; Letícia Almeida de Assunção; Natasha Monte; Esdras Edgar Batista Pereira; et al. (Viruses, 2024)
Coronavirus disease 2019 (COVID-19) is an infection caused by SARS-CoV-2. Genome-wide association studies (GWASs) have suggested a strong association of genetic factors with the severity of the disease. However, many of these studies have been completed in European populations, and little is known about the genetic variability of indigenous peoples’ underlying infection by SARS-CoV-2. The objective of the study is to investigate genetic variants present in the genes AQP3, ARHGAP27, ELF5L, IFNAR2, LIMD1, OAS1 and UPK1A, selected due to their association with the severity of COVID-19, in a sample of indigenous people from the Brazilian Amazon in order to describe potential new and already studied variants. We performed the complete sequencing of the exome of 64 healthy indigenous people from the Brazilian Amazon. The allele frequency data of the population were compared with data from other continental populations. A total of 66 variants present in the seven genes studied were identified, including a variant with a high impact on the ARHGAP27 gene (rs201721078) and three new variants located in the Amazon Indigenous populations (INDG) present in the AQP3, IFNAR2 and LIMD1 genes, with low, moderate and modifier impact, respectively.